1567 A Review of Paediatric Handovers - Are they Safe and Effective?. (October 2012) - Nath, P; Desai, P; Kelsall, W
Abstract : Background: With changing work patterns effective handovers are essential for patient safety and continuity of care. Handovers also provide educational opportunities, to initiate or complete work place based assessments (WPBA), improve communication, management skills to prioritise work. Methods: A 10 point online questionnaire was sent by email to all the trainees and tutors from June - August 2010. Results: Responses were received from 17 trusts (17/18 hospitals, 94%) and from 56 trainees (18 ST1–3 and 38 ST4–8). Feedback was received on a total of 73 handovers: 36% covered both general paediatrics and neonates; 27% general paediatrics only and 23% neonatal intensive care. 78% of respondents were involved in two or more handovers during the working day. 69% of the handovers were lead by consultants or registrars. All the handovers had registrars present, 93% had junior trainees, 82% consultants and 34% had members from nursing team. 69% of the handovers were conducted with the aid of printed sheets. Only 51% of the handovers started on time, 19% were free from distractions by allied professionals and just 4% were 'bleep' free. 64% had some educational activity within the time allocated. WPBAs were initiated or completed in only 3% of handovers. Conclusions: Handover practice varies between hospitals. Most are well organised but many do not start on time and are not free from interruptions. Formal teaching was not a regular feature of handovers and WPBA were rarely initiated or completed. The role of the handover in training could be developed further.